Market Reaction to The Palestinian-Israeli Conflict: Analysis of PT. Unilever - Andini, Nova Riza Ayu; Amal, Muhammad Ahsanul; Iftitah, Insiyatul; Nazmi, Redha Alfin (Institut Agama Islam Negeri Kendari, 2024)
This study aims to analyze the impact of the Palestinian-Israeli conflict on stock market reactions, particularly at PT. Unilever Indonesia, focusing on changes in stock prices and abnormal returns before and after the boycott of Unilever products. This study employs a quantitative approach using an event study method conducted over 14 days, seven days before and seven days after the boycott issue emerged. The analytical techniques used include descriptive statistical tests, the Shapiro-Wilk normality test, and hypothesis testing using the paired sample t-test and the Wilcoxon signed-rank test. The study's results indicate significant differences in stock prices and abnormal returns of PT. Unilever Indonesia before and after the boycott issue, while trading volume activity did not differ significantly. The decline in stock prices and abnormal returns after the boycott issue indicates an adverse reaction from investors toward the company's involvement in the conflict. The implications of this study can provide insights to multinational companies on how global political conflicts can affect corporate image and financial performance through stock market reactions and the importance of more cautious communication strategies and policies in managing corporate involvement in global political issues.